A study on customer satisfaction towards the after sales services in the context of automobiles in chennai - ROBERT. P, WILLIAM; R, RAHUL. (The journal of contemporary issues in business and government, 2020)
In the automobile industry after sale service plays an important role whether it is before buying a product or after buying a product.The main reason of this study is to determine the impact of Customer Satisfaction on after sales services in the context of Automobiles in Chennai and to know about the factors which influences customer satisfaction. The data is collected on probability basis from 71 respondents and is analysed with the SPSS tool. The collected data were classified, tabulated and analysed with statistical tools Frequency analysis, Mean analysis, Independent t Test, One-way Anova and Regression analysis. The results showed that the majority of the respondents were male and of age between 21-30 years who use a car or bike. It is found that Speed of Service and Cost of Service of after sales service is significant on the Customers